Kajian Beberapa Jamur Entomopatogenik pada Ulat Daun Kubis Hijau, Plutella xylostella - Tri Harjaka; Suryanti Suryanti (Universitas Gadjah Mada, 2002)
The use of entomopathogenic fungi for controlling Diamond Back Moth (DBM), Plutella xylostella L. still limited. Even though there are some entomopathogenic fungi could infect DBM. The aim of this research is to know the kind of entomopatogenic fungi on DBM to be used as biological control agent. Some isolates of fungi were collected from DBM infected by the fungi on field in Central Java and Yogyakarta. Fungi infecting DBM was isolated, and cultured on Potato Dextrose Agar (PDA). Purification, identification and infection tests were done to know the potency of each fungal isolates. The results showed thatfive species of fungi infecting DBM, are Beauveria bassiana, Metarhizium anisopliae, Paecilomyces sp. Entomophthora sp.and Hirsutella sp.